Investigative Journalism in Nepal: Practice and Impact - Dahal, Ramjee (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
Investigative journalism has become a matter of growing interest in the wake of expanding practice of journalism in Nepal. For journalists, who are always busy in collecting and communicating news of daily events in society, it is a challenging task in itself to prepare investigative news after longtime study and research on a serious matter. Due to public interest in information and increased access to social media, reaching the depth of news has drawn interest for communication consumers. Events and topics that someone wants to hide or keep secret become public interest. Therefore, it is the main task of investigative journalism to study and inform about such matters of public interest to the society at large. It is also the professional integrity of journalist to expose wrongdoings kept secret. In the present article, the practice of investigative journalism in Nepal and its impact on good governance has been analyzed by adopting the study and explanatory method.